Human resource policies, training and qualifications - Artiles, Antonio Martin [Verfasser]; Miguelez, Faustino [Verfasser]; Lope, Andreu [Verfasser] (My University, 1998)
"The article focuses on the argument that human resource policies set out to develope a twofold approach to management of the workforce which thereby becomes divided between a core of highly qualified and skilled employees and a peripheral component consisting of workers with less or no skills. This split is reflected in company training policies which, furthermore, exhibit an anti-trade union bias." (author's abstract, IAB-Doku)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.2.2.3 Beschäftigungsformen; S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; G 1.2.3.1 Potenziale; I 2.2 Europa; Personalpolitik; Randbelegschaft; Mitarbeiter; Segregation; Betriebliche Weiterbildung; Qualifikation; Europa